Pendampingan Ibu Hamil menuju Persalinan Nyaman dengan rutin Senam Maryam Selama Pandemi - Fitriana, Yuni; Revika, Era (UKInstitute, 2022)
As the pregnancy progresses, the mother's posture adjusts to the heavier uterus. Pain felt by pregnant women in the back causes back pain. Non-pharmacological pain therapy is exercise. Pregnancy exercise is currently known as Maryam exercise. Pregnant women need to meet their needs holistically to prevent anxiety and overcome the discomforts of pregnancy. Maryam gymnastics can reduce stress levels, cortisol levels in pregnant women which are useful in the emergence of adequate uterine contractions during labor so that the duration of labor in the first and second stages is shorter, breastfeeding is smooth, trains abdominal and pelvic muscles and improves sleep quality. Maryam's gymnastics aims to improve the health of the mother and fetus in the face of childbirth. The method of activity is carried out online to answer the challenges of the covid 19 pandemic, the team created a What's Application Video Call Group. Gymnastics is done directly with a certified gymnastic instructor. After Maryam's exercise is carried out, there will be a discussion session for pregnant women to respond and ask questions about her pregnancy. Maryam's gymnastics activities for pregnant women TM II-TM III (16 weeks - 40 weeks) are carried out routinely 2 times a week every Wednesday and Saturday for 4 months. There are 10 participants. Of the 9 participants who gave birth normally there were 7 people and by SC (Sectio Cesarea) there were 2 people on the indication of a narrow pelvis and polyhydramnios and PEB. Maryam's gymnastics is calm in the face of SC surgery and breastfeeding is smooth. There were also participants who succeeded in VBAC (Vaginal Birth After Cesarea). Participants feel the benefits of Maryam exercise, namely the mother feels relaxed, ready to face childbirth comfortably, sleep quality so as to prevent anxiety and stress during pregnancy and relax the muscles of the vagina, abdomen, thighs and back. Therefore, pregnant women must attend every activity of Maryam's gymnastics so that they are able to face childbirth with a calm and happy heart and healthy mothers and babies